Characterization of Plastic Waste in the Kebon Melati Reservoir, Central Jakarta and the Utilization Potential of Polyethylene Terephthalate (PET) - Sari, Mega Mutiara; Suryawan, I Wayan Koko (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study examines the characteristics and utilization potential of plastic waste, particularly Polyethylene Terephthalate (PET), collected from the Kebon Melati Reservoir in Central Jakarta. Urban reservoirs in Jakarta increasingly serve as accumulation points for floating waste, contributing to drainage obstruction and aquatic pollution. Waste samples were collected using a grab sampling method at multiple accumulation points, followed by manual sorting and moisture content analysis. The results showed that biodegradable waste accounted for 64.1% of total collected waste, while plastic waste represented 35.9%. Within the plastic fraction, PET was identified as the dominant polymer type, followed by High-Density Polyethylene (HDPE) and Low-Density Polyethylene (LDPE). Moisture analysis indicated that PET had the lowest moisture content (3.4%) compared with HDPE (5.3%) and LDPE (6.3%), while biodegradable waste had a significantly higher moisture content (78.1%). These findings demonstrate that PET has strong potential for mechanical recycling, pyrolysis, and Refuse-Derived Fuel (RDF) production due to its low moisture content and stable polymer structure. This study highlights the importance of reservoir-based plastic recovery as a strategy to support circular economy initiatives and improve urban waste management in Jakarta.